Commissioned project evaluations of research and innovation policy in Germany: A review - Stefan Büchele; Guido Bünstorf; Uwe Cantner; Lukas Dreier; Petra Meurer; Liam Paul Neumann (Expertenkommission Forschung und Innovation (EFI), 2024)
[Introduction:] The evaluation of policy interventions is an essential tool for reviewing and optimizing policies, especially in the field of research and innovation (R&I) policy (BMWi 2013). Policy evaluations involve systematic analyses to assess the design, implementation, and impact of policy interventions. Their aim is to provide decision makers with evidence-based insights to enhance the achievement of desired objectives. Monitoring and evaluation serve multiple purposes (Gertler et al. 2016): Monitoring of policy interventions through the continuous collection and analysis of information on key indicators aims to assess the quality of the implementation and to track the development of interventions over time. In contrast, policy evaluations are conducted at specific points in time, often with contributions from external experts to ensure an impartial perspective (Gertler et al. 2016). These policy evaluations not only review whether the intervention was successfully implemented but also determine, in the case of impact assessments, whether associated effects can be attributed to the program, i.e. whether the program was effective. Irrespective of the specific policy domain, policy evaluations are important to inform evidence-based policy-making and to assess the impacts of interventions. In the realm of R&I policy, the use of evaluations to facilitate policy learning is particularly important, as R&I policy uses a wide variety of funding approaches, is highly context-specific, and new expectations are raised in the course of tackling major societal challenges. For example, R&I policy operates in the areas of basic research, applied research and product development exhibiting varying degrees of uncertainty, and it addresses different technologies, sectors and regions. In addition, new challenges in R&I policy, such as mission-oriented policies focusing on the directionality of R&I activities, also require new policy designs. The German Federal Budget Code (Bundeshaushaltsordnung, BHO) mandates that all measures with an impact on the federal budget be subject to an appropriate economic feasibility study. According to an administrative regulation linked to the BHO, this economic feasibility study has to include a performance review. The performance review aims to determine whether and to what extent the intended objectives of a policy intervention have been achieved, what the economic efficiency is and whether the policy intervention was actually the cause of the achievement of the objectives. Furthermore, performance reviews should also help to identify needs and opportunities for adjusting the policy intervention. (...)
Keywords: 330; Technology policy; Impact assessment; Germany; Technologiepolitik; Wirkungsanalyse; Deutschland